UNIVERSITY NOTES. (The Accounting Review, 1927)
This article presents information on various universities. The department of economics at Brown University is offering four graduate fellowships for the year 1927-1928. which are open to graduates of any college who have majored in economies or business administration. Professor J. P. Adams will offer a course in public utility regulation at the summer session of Northwestern University and will also be associated with the research activities of the Institute for Research in Land Economics and Public Utilities. A reorganization of the accounting courses is under way at Indiana University. Beginning accounting will be advanced to the sophomore year and will be put on the case basis. A chapter of the N. A. C. A. has just been established in Indianapolis with which the University hopes to cooperate. Under cooperative arrangements at the University of Minnesota, with a number of leading Twin City public accountants, ten seniors in the accounting course are being employed as junior accountants during the winter quarter.